Value Relevance of Accounting Profit: An Extended Analysis in Thailand - Arunrungsirilert , Teerachai; Sangiumvibool-Howell , Payear; Kitticharoenrerk , Pitchaya (Thammasat Review, 2022)
This study aims to compare the value relevance of accounting profit which includes (1) gross profit (GP), (2) earnings before interest, taxes, depreciation, and amortization (EBITDA), (3) earnings before interest and taxes (EBIT), (4) net income (NI), and (5) comprehensive income (CI) as well as components of other comprehensive income (OCI). The study uses multiple regression to analyze 3,311 samples from firms in all 8 industries of the Stock Exchange of Thailand (SET) from 2011 to 2018. The various aspects of value relevance comprising overall, by industry, time lag, and political stability are also studied. Results show that all types of accounting profit positively affect stock price. NI had the most value relevance followed by CI. Results also found that NI had the highest value relevance in most industries. Property, construction, and resources industries had CI as the most value relevance. The acconting profit had the highest value relevance at 16 days after the financial statement submission deadline. Furthermore, political stability had a positive effect on firm value. This positive political variable study exposures to academic literature in value relevance. Moreover, this research result contributes more understanding in firm value for managers and investors.